(untitled) (Comparative & International Education Series, 2022)
Learning can be defined as a relatively permanent change in behavior due to experience (Dewey). Understanding the physiology and the neuroscience of learning is a contribution to science. Psychology provides an understanding of the true nature of personal development and transformation and is essential in realizing human potential. Technology innovations continuously infuse changes in teaching and learning. This has been especially true since the COVID-19 pandemic has stimulated technology use. My purpose is to share insights into the changes and new developments in learning psychology, translate them into positive learning opportunities, and relate them to online and distance learning. How to cite in APA: Luskin, B. (2022). Media psychology and the online learning experience “neurons that fire together wire together”. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 47-52). STAR Scholars.